MAXIMUM ENTROPY MODEL FOR PREDICTION OF SMALL PELAGIC FISHING GROUNDS IN THE JAVA SEA (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
The optimization of small pelagic fishing in the Java Sea can still be improved by the development of fishing area information systems. This study aims to predict small pelagic fishing grounds using the Maximum Entropy (MaxEnt) model. The data used in this study are environmental data in the form of sea surface temperature (SST) and sea surface salinity year 2018 in the Java Sea downloaded from Google Earth Engine via RStudio and fishing vessel position data downloaded from VIIRS Boat Detection (VBD). The MaxEnt model showed good performance with an AUC value of 0.849. The response curve shows the highest probability of fish distribution being at SST in the range of 27.0 – 31.0 oC, and salinity of 32 – 34 psu. The predicted map of fishing areas produced by MaxEnt modeling in the form of a habitat suitability map showed that parameter salinity had an effect of 94.5% and SST of 5.5%. Peta fish habitat suitability shows that the majority of fishing vessel coordinates are at the Habitat Suitability Index (HSI) value of 0.5 – 0.8. Small pelagic fishing areas are concentrated in the central and northern regions of the Java Sea approaching the southern waters of Borneo Island.